Synthesis and Thermal Decomposition Kinetics of Gd(III) Complex with Unsymmetrical Schiff Base Ligand - Bi, Shuangyu; Zuo, Jian; Zhang, Nan; Zhang, Pengfei; Zhang, Zhen; Fan, Yuhua (Asian Journal of Chemistry, 2013)
A new unsymmetrical solid Schiff base (LLi) was synthesized using L-lysine, o-vanillin and 2-hydroxy-l-naphthaldehyde. Solid gadolinium(III) complex of this ligand [GdL(NO3)]NO3·2H2O has been prepared and characterized by elemental analyses, IR spectra, 1H NMR spectra, UV spectra and molar conductance. The thermal decomposition kinetics of the complex for the second stage was studied under non-isothermal condition by TG and DTG methods. The kinetic equation may be expressed as: da/dt = Ae-E/RT(1-a)2. The kinetic parameters (E, A), activation entropy DS¹ and activation free-energy DG¹ were also gained.